Core–shell metal–organic frameworks with pH/GSH dual-responsiveness for combined chemo–chemodynamic therapy. Issue 88 (19th October 2022) - Dong, Junliang; Ma, Ke; Pei, Yuxin; Pei, Zhichao
Abstract : A novel core-shell metal-organic framework (MOFs), Cu-MOF@SMON/DOX-HA, was fabricated for chemo-chemodynamic combined therapy to achieve efficient drug targeting delivery and induce cells ferroptosis. Abstract : A novel core–shell metal organic framework (MOF), Cu-MOF@SMON/DOX-HA, was fabricated using 3-amino-1, 2, 4-triazole (3-AT) and organosilicon for combined chemo–chemodynamic therapy with high drug-loading capacity, pH/GSH dual-responsiveness, and good biocompatibility. The Cu-MOF@SMON/DOX-HA could not only generate reactive oxygen species, but also effectively consume glutathione (GSH) to induce cell ferroptosis. This work involves the modification of organosilicon on the surface of MOFs, which possess good performance in high drug-loading ability and pH/GSH dual-responsive degradation for combined chemo–chemodynamic therapy.